25‐Hydroxyvitamin D Levels and Markers of Subclinical Myocardial Damage and Wall Stress: The Atherosclerosis Risk in Communities Study. Issue 11 (7th November 2016) - Michos, Erin D.; Selvin, Elizabeth; Misialek, Jeffrey R.; McEvoy, John W.; Ndumele, Chiadi E.; Folsom, Aaron R.; Ballantyne, Christie M.; Lutsey, Pamela L.
Abstract : Background: Low 25‐hydroxyvitamin D (25[OH]D) is associated with increased cardiovascular disease risk. Less known is whether 25(OH)D deficiency contributes to subclinical myocardial damage and wall stress (high‐sensitivity cardiac troponin T [hs‐cTnT] and N‐terminal pro–brain natriuretic peptide [NT‐proBNP]) or whether associations vary among subgroups. Methods and Results: Overall, 11 311 Atherosclerosis Risk in Communities participants without prevalent cardiovascular disease had 25(OH)D, hs‐cTnT, and NT‐proBNP measured at baseline (1990–1992), and 8990 had measurements of hs‐cTnT and NT‐proBNP repeated 6 years later. We examined associations of deficient 25(OH)D (<20 ng/mL) with prevalent elevated hs‐cTnT (≥14 ng/L) and NT‐proBNP (≥100 pg/mL), change in hs‐cTnT and NT‐proBNP, and incident elevated hs‐cTnT and NT‐proBNP. We tested for interactions by age (<56 and ≥56 years), sex, and race. In fully adjusted models, 25(OH)D was not associated with prevalent elevated hs‐cTnT and NT‐proBNP. Deficient 25(OH)D, however, was associated with increased 6‐year change in hs‐cTnT (β=0.54 ng/L [95% CI 0.08–1.01]) but not change in NT‐proBNP. Deficiency in 25(OH)D was not associated with incident elevated hs‐cTnT in the overall cohort but was associated with incident elevated hs‐cTnT in younger but not older adults (relative risk 2.18 [95% CI 1.21–3.94] versus 0.78 [95% CI 0.56–1.08], respectively; P =0.01 for interaction by age). Deficient 25(OH)D was also associated with incident elevated NT‐proBNP in men but not women ( P =0.01 for interaction by sex). Conclusions: Vitamin D deficiency was associated with increased 6‐year change in hs‐cTnT levels. Hypothesis‐generating differences in associations by age and sex, but not race, were observed. If these associations are causal, further research is needed to understand mechanisms by which low 25(OH)D confers increased risk in these subgroups and whether treating deficient 25(OH)D can prevent myocardial damage and wall stress.